Challenges associated with implementation of inclusive education in Early childhood education classrooms: the case of Tategulu primary school. - Ndlovu, Sithabile (Midlands State University, 2019)
This study was carried out at Tategulu Primary school in Cowdray Park cluster under Reigate district with the aim of finding out the challenges associated with the implementation of inclusive education in ECE classrooms. The researcher used a case study design. Interviews and observations were used to gather data. The target population comprised of teachers and parents at Tategulu Primary school. However a sample of 10 participants was randomly chosen comprising of 5 teachers and 5 parents. Mainly the descriptive statements were used for presentation and analysis of data. The study revealed that several challenges were faced at Tategulu Primary school ECE classrooms in an effort to effectively implement inclusive education. The study indicated that lack of skills and knowledge on the part of the teacher, and limited resources were the major barriers in implementing inclusive education in ECE classrooms. However the study brought some constructive strategies such as parental involvement and the change of curriculum to cater for learners with disabilities. The study concluded that facilities and resources in most ECE classrooms were not constructed with learners with disabilities in mind. Further the study revealed that the teacher pupil ratio was too high resulting in teacher’s failure to give each learner individual attention. Finally the study recommended that training of ECE teachers in special needs was essential in order to make inclusive education in ECE a success.